Interest development and learning in choice-based, in-school, making activities: The case of a 3D printer. (December 2019) - Ramey, Kay E.; Stevens, Reed
Abstract: Integrated STEAM (science, technology, engineering, arts, and math) making activities have become increasingly popular in recent years. Many tout their benefits for STEAM interest development. However, we know relatively little about how these activities cultivate STEAM interests or about the relation between interest development and learning. This paper examines these issues in the context of one set of in-school, choice-based, STEAM making and learning environments, FUSE Studios. Drawing on sociocultural approaches to interest development, we present the case of one student's interest pathway through FUSE. By the end of the schoolyear, this student had developed an interest in and was recognized as a relative expert at 3D printing. She also connected this interest in 3D printing to a career aspiration to "help cancer kids and become a doctor for them". Drawing on ethnographic observations and microanalysis of video-recordings, we trace her year-long interest pathway through FUSE to understand how her interests, in interaction with the socio-material context of FUSE, shaped her learning. We argue that the choice-based nature of FUSE allowed her to pursue her interests, organize her own learning, and consequently, cultivate STEAM interests and learning.